Music and narrative: linking vessels in the construction of a subject reader (Papeles, 2017)
The present article offers a deep reflection upon the link between music and narrative through a path which leads to a classroom strategy which takes into consideration these disciplines to make a reader more competent. It also intends to analyze the effect that music has in the brain as well as its multiple possibilities may be shared with literature, which benefit the cognitive development in order to achieve an optimal reading comprehension. Aims to achieve a true consciousness, regarding an interdisciplinary search in the practice and an effective link between knowledge areas, heading toward specific objectives which foster the construction and learning of the knowledge are, undoubtedly, the foundations that frame the ideas spread in this article.
Keywords: music; narrative; cognitive skills; strategy; reading comprehension